PENGELOLAAN KEGIATAN EKSTRAKURIKULER DUTA UNTUK MENINGKATKAN PRESTASI NONAKADEMIK DI SMA NEGERI 3 PATI - Anita Nurdi Hapsari; Eko Handoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The interest of students at SMA Negeri 3 Pati in participating in the DUTA extracurricular program is very high; however, although SMA Negeri 3 Pati is the only school in Pati Regency that provides this program, the best achievements have not yet been attained. This study aims to investigate how the DUTA extracurricular program is managed at SMA Negeri 3 Pati to improve students’ non-academic achievements. The research employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation. Data analysis was carried out through data condensation, data display, and conclusion drawing and verification. The findings indicate that the management of the DUTA extracurricular program has been implemented systematically and strategically through four stages: planning, implementation, supervision, and evaluation. The planning stage is reflected in the preparation of training programs tailored to students’ needs. The implementation stage is conducted systematically and contributes to improving students’ self-confidence, communication skills, and achievements, although it still faces several obstacles such as limited training time, unstable attendance, and insufficient additional funding. Supervision is carried out by the mentors to monitor discipline, participation, and the development of participants’ abilities. Evaluation is conducted through the assessment of training outcomes, performance quality, and achievements in various competitions. The SIMANTAP program in managing the DUTA SMAGA extracurricular activities demonstrates collaboration between the school and parents to enhance students’ non-academic achievements through continuous guidance, support, and monitoring.